(untitled) (BIRDEM Medical Journal, 2024)
Background: Diabetic retinopathy is a complication of diabetes caused by high blood sugar level affecting the eyes. The duration of diabetes appears to be an important risk factor for fractures. Chronic hyperglycemia is widely documented to have an effect on bone health, causing fragility, mechanical strength decrease and an increased susceptibility to fracture due to altered bone matrix microstructure and aberrant bone cell function, despite normal or increasing bone mineral density (BMD). The purpose of this study was to see the relation between duration of diabetes mellitus and BMD in postmenopausal female diabetic patient with diabetic retinopathy. Methods: This cross-sectional study was conducted at the Department of Ophthalmology, BIRDEM General Hospital, Dhaka, Bangladesh during June 2019 to March 2021.After completing their entire ophthalmic examination, 68 post-menopausal female patients between the age of 45 and 70 who had type 2 diabetes with or without diabetic retinopathy (34 in each group) were chosen by using a non-probability sampling technique. After receiving informed written consent, they underwent BMD testing (of lumber spine and femoral neck) at the Institute of Nuclear Medicine and Allied Science (INMAS) by using dual energy x-ray absorptiometry. Results: The mean BMD of lumbar spine was found -2.25±0.91 in diabetic retinopathy group and -1.69±0.99 in without diabetic retinopathy group. The difference was statistically significant (p<0.05). The mean BMD of femoral neck was found -2.4±0.9 in diabetic retinopathy group and -1.9±1.1 in without diabetic retinopathy group. The difference was statistically significant (p<0.05). There was a negative correlation between the duration of diabetes mellitus and the BMD of the lumbar spine (r= -0.699; p=0.001) and the femoral neck (r= -0.695; p=0.001) in diabetic retinopathy patients. There was a negative correlation between the duration of menopause and the BMD of the lumbar spine (r= -0.405, p= 0.018) and the femoral neck (r= -0.395, p= 0.021) in diabetic retinopathy patients. There was also a negative correlation between the duration of diabetes mellitus and the BMD of the lumbar spine (r= -0.418; p=0.014) and the femoral neck (r= -0.384; p=0.025) in without diabetic retinopathy patients. Negative correlation was also found between the duration of menopause and the BMD of the lumbar spine (r= -0.785; p=0.001) and the femoral neck (r= -0.802; p=0.001) in without diabetic retinopathy patients. But in case of diabetic retinopathy patient there was more statistically significant reduction of BMD with increasing duration of DM. Conclusion: Patients with diabetes mellitus for a longer period of time with diabetic retinopathy have considerably lower lumbar spine and femoral neck BMD than patients without diabetic retinopathy. BIRDEM Med J 2024; 14(1): 16-22